The Effectiveness of Learning Dolanan Song and Traditional Javanese Games on Early Childhood Character Development - Susilowati, Dwi; Sugiyo, Sugiyo; Sutarto, Joko (Universitas Negeri Semarang, 2021)
One aspect of child development that is expected by parents is the development of strengthening the child's character, especially with the rapid development of technology in the era of globalization. Thus, Kindergarten teachers apply the learning of dolanan songs and traditional Javanese games for the development of the character of early childhood children. This study aims to analyze the effectiveness of dolanan song learning and traditional Javanese games on early childhood character development and the differences between the two in early childhood character development. The research method used is an experimental method with a quasi-experimental research type. The design used was the pretest and posttest groups. The research population is all children as many as 59 children. Sampling using purposive sampling technique. Data collection using observation and interviews as supporting data. Observations were made to observe the character of the child before and after the treatment. Data analysis used statistical calculations Mann-Whitney test (Wilcoxon). The results of the study indicate that learning processed song and traditional games is effective in developing the character of self-confidence and responsibility in early childhood. The increase in children's character after dolanan song learning was 30.14 greater than the increase in children's character after traditional games of 27.37.